Rumah Radakng sebagai Ikon Pariwisata Budaya di Pontianak Kalimantan Barat - Listia Prihatink; Arkanudin Arkanudin; Dahniar Th Musa (Universitas Tanjungpura, 2021)
The research aimed to describe anthropological socio-cultural phenomena in observing the existence of Rumah Radakng for tourists. This research used ethnographic method and qualitative descriptive approach with the problem related to culture. Data collection was conducted using observation, in-depth interview, and documentation. The research was conducted in Dayak traditional house, Rumah Radakng in Pontianak. Based on the data obtained, Rumah Radakng functions as an alternative for cultural tourism in introducing cultural manifestation as a center of Dayak cultural activities. Currently, Rumah Radakng functions as an icon of cultural tourism in Pontianak. In addition, Rumah Radakng served as an educational media and a means to spread cultural existence in Kalimantan, especially Dayak culture. The existence of Rumah Radakng in Pontianak has caused local and foreign tourists to visit in order to see hoe Dayak house is in Kalimantan. The tourists who would like to learn and understand local culture such as traditions, customs and uniqueness are the expected feedback when traveling. Pontianak Rumah Radakng has a potential as a destination for cultural tourism in providing knowledge, philosophy and values of Dayak culture.